Effectiveness and application of ozone in dentistry – endodontic review (Ozone Therapy Global Journal, 2020)
Ozone is an allotropic modification of oxygen, composed of three oxygen atoms. It is one of nature’s molecules with greater oxidizing power, being able to react with organic and inorganic compounds. Its potent antibacterial and anti-inflammatory properties have been widely used in the medical field, including dentistry. Ozone can be applied to oral cavity in the form of ozonated water, ozonized oil and oxygen/ozone gas. The capacity and effectiveness of ozone has been shown to be a very promising tool in minimal intervention dentistry as well as in canal disinfection.This article presents a brief review of the properties of ozone and its application in dentistry, with a principal focus on its use in root canal treatment. The information for this work was based on books and bibliographic research in medical databases (pubmed / medline).